1994
DOI: 10.1128/aac.38.8.1773
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relationship between soxRS and mar loci in promoting multiple antibiotic resistance in Escherichia coli

Abstract: Multiple antibiotic resistance in Escherichia coli has typically been associated with mutations at the mar locus, located at 34 min on the E. coli chromosome. A new mutant, marC, isolated on the basis of a Mar phenotype but which maps to the soxRS (encoding the regulators of the superoxide stress response) locus located at 92 min, is described here. This mutant shares several features with a known constitutive allele of the soxRS gene, prompting the conclusion that it is a highly active allele of this gene. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
94
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(96 citation statements)
references
References 26 publications
2
94
0
Order By: Relevance
“…In addition, multiple copies of aarP in E. coli resulted in a threefold increase in the accumulation of ␤-galactosidase from an nfo-lacZ fusion, which is normally activated by the SoxS protein (37). This level of activation is similar to that previously reported for MarA, which was capable of activating an nfo-lacZ fusion twofold (26).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…In addition, multiple copies of aarP in E. coli resulted in a threefold increase in the accumulation of ␤-galactosidase from an nfo-lacZ fusion, which is normally activated by the SoxS protein (37). This level of activation is similar to that previously reported for MarA, which was capable of activating an nfo-lacZ fusion twofold (26).…”
Section: Discussionsupporting
confidence: 71%
“…In contrast, marA is the second member of the three-gene marRAB operon (8). In addition, accumulation of the aarP transcript was not increased by exposure of cells to salicylate, a potent inducer of marA (9,26). Therefore, an alternative possibility is that aarP has a cellular role unrelated to antibiotic resistance but is capable of cross-activating genes in the mar regulon manner similarly to SoxS, presumably as a result of the extensive amino acid identity in the helix-turn-helix regions of AarP and MarA (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings provide suggestive evidence for a pu- The exact mechanisms for the overlapping regulation by MarA and SoxS are still poorly understood. Multiple-antibiotic resistance encoded by the soxRS locus appeared partly dependent on an intact mar locus; strains overexpressing SoxS showed increased levels of marRAB transcription (41). On the other hand, other work showed that regulation of some genes by mar and by soxRS can occur through independent pathways, e.g., inaA (46).…”
Section: Resultsmentioning
confidence: 97%
“…SoxS is the activator of the soxRS regulon (17), which mediates a cellular response to oxidative stress and, like MarA, is a member of the XylS/AraC family of transcriptional activators (20). Many oxidative stress genes, which are known to respond to SoxS, are also responsive to MarA (30,41). Conversely, SoxS is able to confer a Mar phenotype via activation of genes that are under the control of MarA (4,25).…”
Section: Resultsmentioning
confidence: 99%